The Effect of Clove's and Lemongrass's Essential Oil in Basal Feed on Performances and Hematology Profile of Streptozotocin-Induced Diabetic Rat - Baidlowi, Ahmad; Nesti, Dela Ria; Tjahajati, Ida (Faculty of Veterinary Medicine Universitas Brawijaya, 2019)
This research was conducted to determine the effect of Clove’s and Lemongrass’s essential oil (EO) in basal feed on performances and hematology profile of Sterptozotocin-induced diabetic rat. 20 rats aged 40 days were divided into four groups of feed treatments, which are: negative control feed (basal feed-non-diabetic) (R1); positive control feed (commercial diabetic food) (R2); basal feed+Clove’s EO (R3); and basal feed+Lemongrass’s EO (R4). Each treatments using 5 rats. Collected data were performances and blood hematology profile. Data were analyzed using one way ANOVA design, the significance of different was tested using Least Significant Different (LSD) test. The result from this research showed that Clove’s and Lemongrass’s EO were significantly affected (P<0.05) on post-induction initial weight (5.41%; 3.30%; and 5.21%) compared to R2 group. It also significantly affected (P<0.05) on total gain (56.66% and 3.30%) and final weight (5.47% and 3.48%) compared to R1 group. Hematology profile’s data showed that both of Clove’s and Lemongrass’s EO did not affect to erythrocyte level, however, Clove’s EO did significantly affect to thrombocyte, hemoglobin and leukocyte level compared to R2 group, consecutively: (25.70%; 87.79%; and 37.59%), while Lemongrass’s EO significantly affected hemoglobin level (51.17%) compared to R2 group. It can be concluded that the addition of Clove’s and Lemongrass’s EO on basal feed could maintain the performance and improve the hematology profile of diabetic rat.